2017
DOI: 10.1002/adma.201702888
|View full text |Cite
|
Sign up to set email alerts
|

Capturing “Extraordinary” Soft‐Assembled Charge‐Like Polypeptides as a Strategy for Nanocarrier Design

Abstract: The rational design of nanomedicines is a challenging task given the complex architectures required for the construction of nanosized carriers with embedded therapeutic properties and the complex interface of these materials with the biological environment. Herein, an unexpected charge-like attraction mechanism of self-assembly for star-shaped polyglutamates in nonsalty aqueous solutions is identified, which matches the ubiquitous "ordinary-extraordinary" phenomenon previously described by physicists. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 68 publications
1
31
0
1
Order By: Relevance
“…[72] Vicent and coworkers took a step further, and investigated the exchange rate among star-shaped polyglutamates carriers exclusively labelled with either Cyanine3 or Cyanine5 using dual-colour STORM imaging. [73] The authors for the first time reported on the slow selfassembly of nanocarriers induced by the attraction of polyions at low salt content. This 'extraordinary' charge-like aggregation mechanism was theoretically predicted for such disordered soft materials, but had not yet been observed experimentally.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[72] Vicent and coworkers took a step further, and investigated the exchange rate among star-shaped polyglutamates carriers exclusively labelled with either Cyanine3 or Cyanine5 using dual-colour STORM imaging. [73] The authors for the first time reported on the slow selfassembly of nanocarriers induced by the attraction of polyions at low salt content. This 'extraordinary' charge-like aggregation mechanism was theoretically predicted for such disordered soft materials, but had not yet been observed experimentally.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The large conjugate size (30-100 nm) does not support glomerular filtration as mechanism of urinary excretion of the unprocessed molecule. Moreover, published detailed pharmacokinetic studies showed plasma clearance of 1.193 ml/h and in vivo distribution of St-PGA in healthy mice characterized by efficient renal uptake and a wide organ distribution, including accumulation in immune cells of lymphoid organs 28,29 , which could be potentially important to control deregulated proinflammatory activity during AKI. Kidney St-PGA accumulation was already detected at 30 min, peaked at 8 h and remained significantly retained after 72h 29 , which could account for the in vivo St-PGA-CL-BDMC inhibitory effects during AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of tubulointerstitial injury including pyknosis/apoptosis, activity, proliferation/regeneration, flattening, necrosis, calcifications and intratubular precipitations were individually scored on a semiquantitative scale from 0 to 3. Results from each item were added to yield the overall tubular injury score (maximal value 21) as previously described 29 .…”
Section: Gene Expressionmentioning
confidence: 99%
“…18 Some studies attempted to combine BTA-cores with poly-amino acid derivatives; however, BTA played the role of a multifunctional core rather than supramolecular motif in all cases. [18][19][20] Besenius pioneered a method of charge screening for small BTA-based molecules bearing ionizable groups with low molecular weight salts, achieving control for up to nine charges for Newkome dendron-decorated molecules. 21 We hypothesized that replacing Newkome dendrons with small PGA chains should allow the formation of stable structures that can self-assemble in water and other physiological solutions.…”
Section: Introductionmentioning
confidence: 99%